I was reading 'Category Theory for Programmers' by Bartosz Milewski and got really confused by the implementation of bimap in
class Bifunctor f where bimap :: (a -> c) -> (b -> d) -> f a b -> f c d bimap g h = first g . second h first :: (a -> c) -> f a b -> f c b first g = bimap g id second :: (b -> d) -> f a b -> f a d second = bimap id
This is the definition of the
Bifunctor typeclass taken directly from the library Control. If
bimap evaluates to
second, which in turn evaluates to
bimap itself, how is this supposed to end? Could you please explain how the evaluation of
bimap works? Thank you!